Muscle recruitment sequence and total reaction time during a karate roundhouse kick - Hu, C.-C.; Li, J.-D.; Hsieh, F.-H.; Lu, T.-W. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of the current study is to quantify the muscle recruitment sequence and total reaction time of fourteen national karate athletes and fourteen college karate athletes while performing upper level roundhouse kick. A 16-channel electromyography was used to measured the muscle activities and an instrumented target was for the evaluation of the response time. The experimental results show that both groups recruited the biceps femoris on the kicking (right) side, followed by the right gastrocnemius, but the subsequent muscle firing sequence was slightly different. This resulted in smaller total reaction time of the national group (736.32 ms) than the time of the control group (770.28 ms) because of different across skill level.